Strain gauge measurements on a full scale tidal turbine blade - Thomas Lake (Renewable Energy, 2021)
The development of tidal energy converters, and particularly floating tidal energy converters, is an area of increased development in recent years. Testing of a floating tidal energy device over winter 2017/18 led to an opportunity to record and examine strain of a full scale composite turbine blade under operational conditions, with comparison of generating and parked behaviours. Comparison of the recorded data shows that blade strain correlates well with both torque and thrust over the averaging periods specified in IEC62600-200, although examination of frequency spectra generated from the strain data show that higher frequency fluctuations in strain are not necessarily detectable in the larger scale thrust and torque recordings with this particular measurement arrangement. The need for well synchronised clocks on recording systems is also highlighted, along with a cross-correlation method used to recover the alignment of data from different systems to allow comparison between them over periods of a similar order of magnitude to the clock skew between the systems.